Proposed new design and schemes for C&S Gazebo Restaurant at Jalan Sultan Azlan Shah 31150, Ipoh Perak / Ekmelluddin Firdaus Khirdzir - Khirdzir, Ekmelluddin Firdaus (Faculty of Architecture, Planning and Surveying, 2006)
The main objectives of this project is to proposed a new design and schemes for Canai & Such Gazebo. Under the restructuring programs, the point is to break away from the Traditional image of Malaysian restaurant and stalls, where hygiene and food quality was not to the authority's required standards. In order to achieve that, Canai & Such adopted a very stringent practice by setting up a special division to monitor standards of hygiene and cleanliness both in the areas of preparation and serving. The main focus was to design and operate a Central Kitchen equipped with modem and efficient food preparation and cooking facilities. The goal was to maintain a consistent taste and good quality food to all its guests patronizing restaurant. The observation and an interview had been conducted in order to collect relevant information. A set of sample (questionnaires) had been distributed to various target group such as public and local restaurant.